Aedes aegypti anti-salivary proteins IgG levels in a cohort of DENV-like symptoms subjects from a dengue-endemic region in Colombia - Olajiga, Olayinka M.; Marin-Lopez, Alejandro; Cardenas, Jenny C.; Gutierrez-Silva, Lady Y.; Gonzales-Pabon, Maria U.; Maldonado-Ruiz, L. Paulina; Worges, Matt; Fikrig, Erol; Park, Yoonseong; Londono-Renteria, Berlin (Frontiers in Epidemiology, 2022)
Dengue fever, caused by the dengue virus (DENV), is currently a threat to about half of the world's population. DENV is mainly transmitted to the vertebrate host through the bite of a female Aedes mosquito while taking a blood meal. During this process, salivary proteins are introduced into the host skin and blood to facilitate blood acquisition. These salivary proteins modulate both local (skin) and systemic immune responses. Several salivary proteins have been identified as immunogenic, and some of them display immunomodulatory properties enhancing arboviral infections. Immune responses against the salivary gland extract (SGE) and Nterm-34kDa peptide have been characterized as a biomarker of human exposure to mosquito bites while AgBR1 and NeSt1 proteins have shown modulatory properties during Zika virus (ZIKV) and West Nile virus infections and antibodies against them have shown protection or a delay in infection. Since DENV is also a Flavivirus closed related to ZIKV, we were interested in evaluating whether IgG antibodies against AgBR1, NeSt1, Nterm-34kDa peptide, and SGE were associated with DENV infections. For this, we tested two hundred and one serum samples from volunteers living in a dengue fever endemic area in Colombia in 2019 using an ELISA test to measure IgG antibody levels. This pilot study is important to establish the involvement of antibody responses against salivary proteins in dengue disease progression.